PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN (STUDI PADA ALPHA HOTEL PEKANBARU) - Icha Sembiring; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to determine the Effect of Promotion and Service Quality on Customer Satisfaction (Study on Alpha Hotel Room Services Pekanbaru). Where two independent variables and one dependent variable are proposed, namely Promotion and Service Quality as independent variables and Consumer Satisfaction acts as the dependent variable. The population in this study were Alpha Hotel Pekanbaru Visitors with a sampling of 100 people calculated using the Slovin formula and the technique used Accidental sampling. The results of the analysis use validity test, determination test, simple linear regression test, multiple linear regression test, t test, and f test so that it can be seen that Promotion has a significant effect on Consumer Satisfaction in Pekanbaru Hotel Room Service, Service Quality has a significant effect on Consumer Satisfaction Alpha Hotel Pekanbaru Room Services, and Promotion and Service Quality have a significant effect on Consumer Satisfaction at the Alpha Hotel Pekanbaru Room Service. Keywords: Promotion, Service Quality, Consumer Satisfaction